Fake leadership influence on organizational destruction in Higher Education Institutions (HEIs). - Agnieszka Bieńkowska; Katarzyna Tworek (PLoS ONE)
The role of leadership in Higher Education Institutions (HEIs) is pivotal. While much research emphasizes the beneficial effects of leadership, the negative impacts of destructive leadership styles remain less explored. This paper investigates the concept of fake leadership - a form of destructive leadership characterized by leaders' intent to engage in harmful behaviors while maintaining a facade of authenticity - and its influence on organizational destruction in HEIs. Drawing on the Toxic Triangle Framework, this study examines how fake leadership undermines intra-organizational trust and job performance, ultimately fostering systemic inefficiencies and organizational decline. The two-step empirical study was conducted with 529 employees from HEIs across Europe (France, Poland, Spain, and the United Kingdom) to verify the hypotheses. Statistical reasoning was based on linear regression analysis with mediators. The results confirmed that fake leadership significantly and positively influences organizational destruction. This effect is mediated by a decline in intra-organizational trust and job performance. This study contributes to the literature by introducing fake leadership as a distinct destructive leadership style in HEIs, providing a tailored framework for understanding its role in enabling organizational destruction, and underscoring the critical role of diminished intra-organizational trust and job performance in deepening these adverse effects. Practical implications emphasize the need for ethical leadership, rigorous selection processes, and proactive measures to safeguard institutional integrity and resilience.